(untitled) (Theatrum historiae, 2011)
This work deals with Pope Alexander VII, whose original name was Fabio Chigi (pontificate 1655–1667) and his relation to the Bohemian Lands, especially his role in the establishment of the diocese in Hradec Králové in 1664. In this way, it is an attempt to point out a different view of Czech affairs, i.e. Rome’s view. The work draws on archive documents located in the National Archive in Prague, in the State’s Regional Archive in Zámrsk, the Secret Archive of the Vatican as well as any editions and literature available. Pope Alexander VII was an experienced diplomat with ties both to Germany and Bohemia, which also had an impact upon the matters concerning the establishment of the Diocese in Hradec Králové. As an Apostolic Nuncio in Cologne and a special papal emis- sary in Münster he participated in the negotiations of the Peace of Westphalia (1648) and other related treaties and had already established contacts in the Bohemian Lands. The circles of his friends included mainly Bernard Ignaz of Martinitz and Juan Caramuel of Lobkowitz; however, he also kept in touch with Cardinal Harrach, the Archbishop of Pra- gue, or the Capuchin Valerian Magni. All of these figures as well as some others influenced Chigi and kept him informed about the political situation in Bohemia. These messages, sent not only through official channels, informed the Pope about the religious and political problems related to the establishment of new dioceses in Bohemia.